Training and performance: The mediating role of organizational learning - María Isabel Barba Aragón; Daniel Jiménez Jiménez; Raquel Sanz Valle (BRQ Business Research Quarterly, 2014)
Although there is a general recognition in the literature that training improves a firm's performance, empirical research does not always provide evidence to support this effect. One possible explanation is that training does not have a direct effect on performance but an indirect effect by improving other organizational outcomes. This paper suggests that organizational learning is one of those variables and that it mediates the relationship between training and performance and that the adoption of a learning-oriented training enhances performances through its positive effect on organizational learning. Using a sample of Spanish firms we obtain empirical evidence, which supports the view that this mediating effect is present."
Keywords: 650; Training; Performance; Organizational learning; Mediation